A toponímia da cidade de Ladário/MS: interfaces entre léxico, cultura e história - WANDERLEY RENAN CARMO DOS SANTOS (2023)
Toponymy, a linguistic discipline linked to Onomastics, provides foundations for the analysis of the names of places, toponyms, particularly for the study of the motivation, etymology and structure of these names, in addition to favoring the highlight of historical and social aspects of a place. Inserted in the field of toponymic studies, this research presents the results of the study on the urban toponymy of the city of Ladário/MS. The general objective of the research was to study the toponyms that name the public places (avenues, streets, squares, etc.) of the city of Ladário/MS, including the toponyms related to the 11 neighborhoods of the city: Centro, Santo Antonio, Boa Esperança, Almirante Tamandaré , Seac, Mista, Alta Floresta I, Alta Floresta II, Mutirão, Nova Aliança and Potiguar. As for the specific objectives settled: i) catalog the toponyms that name the public places of the city of Ladário/MS, from consultation to maps and/or official letters of the city; ii) analyze the toponyms that make up the corpus from the points of view of motivation, the language of origin and the structure of toponymic phrases, fundamentally adopting the theoretical model of Dick (1990; 1992); iii) classify the toponyms according to Dick's (1992) taxonomic model, seeking to outline an overview of the trends in the studied toponymy; iv) examine sociolinguistic-cultural conditions that served as motivation and/or denominative cause for naming the public places in the city of Ladário/MS; v) verify, through oral research, the denominative causes of the toponyms and the possible existence of a parallel toponymy; vi) describe, based on ethnolinguistic postulates, the question of the relationship between lexicon, culture and history in the toponymy under study. Data were extracted from official maps made available by the Municipal Administration Secretariat, scale 1:20000, accounting for 170 toponyms that make up the study corpus. The analysis was based on theoretical and methodological assumptions of Toponymy, in special the studies of Dick (1990, 1992, 1996, 1999, 2001, 2004, 2007); Oliveira (2014); Bittencourt (2015); Cavalcante (2016); Amorim (2017); Neves (2019); from the Lexicology, Biderman (1998, 2001); from the Etnolinguistic, Sapir (1969); Casado Velarde (1991); and from the Linguistic Antropology, Duranti (2000).The study results point to the predominance of names of an anthropocultural nature (76.92%) to the detriment of names of a physical nature (23.07%). The most recurrent taxonomy in this study was anthropotoponyms (33.33%), followed by axiotoponyms (19.49%) and historiotoponyms (10.06%). The occurrence of these taxonomies reinforces facts evidenced by studies of the same nature: the tendency to honor people recognized or not in society, however, it is necessary to highlight the high rate of occurrences of phytotoponyms (16.98%) concentrated in two neighborhoods. The data confirm the influence of the military presence in Ladário, given that the most recurrent taxonomies refer to personalities, titles and historical events related to the Brazilian Navy. In addition, it is observed that the Pantanal flora can be served as a motivation for the denomination of most of the public places in the city, since the city is located in a geography immersed in this biome. In summary, the study contributed to show that urban toponymy records facts of the population's experience, acting as a photograph of history and culture, as a way of perpetuating the collective memory of a place, keeping it alive for future generations.